Working out of the high school strategy as a necessary condition of optimization of a control system experts' vocational training (Путеводитель предпринимателя)
The article considers methodological aspects of working out of the high school development strategy. The strategy assumes a modification of a control system of the vocational training which is considered as a totality of subsystems providing: a) management of a set of entrants; b) management of process in vocational training; c) management of the graduates' employment. A change of approach to financing of high schools should consider a necessity of financing of each subsystem.